The Classroom Curriculum Development for National Aviation Security Instructor - Yiyan , Zhang; Lertlit, Supinda (Journal of Roi Kaensarn Academi, 2024)
The study aimed to identify the objectives related to the National Aviation Security Instructor Curriculum (NASIC), employing Outcome-Based Education (OBE) principles and the ADDIE (Analysis, Design, Development, Implementation, Evaluation) Model, and to evaluate the effectiveness of the NASIC implementation. The methodology included mixed research methods, both quantitative and qualitative, utilizing three rounds of Delphi surveys to determine the competencies of National Aviation Security Instructors (NASI). The development of NASIC was based on the analysis of expert opinions, utilizing various criteria such as positive coefficient, concentration of opinions, expert authority coefficient, and expert coordination coefficient. This process resulted in the identification of 33 competencies for NASIs. To evaluate the effectiveness of the curriculum, an experiment was conducted, involving both an experimental group and a control group. The study ensured there were no significant baseline differences between the two groups concerning demographics and background variables. The evaluation of the curriculum’s effectiveness was carried out across three dimensions: knowledge, skills, and attitudes. Statistical analysis, including Chi-square tests and Mann-Whitney U tests, was performed on the data collected from both groups. The results indicated statistically significant differences between the experimental and control groups across all three areas of knowledge, skills, and attitudes, suggesting that the NASIC implementation had a positive impact. These findings provide a framework for future research in applying OBE concepts and the ADDIE model to other aviation curricula.